TIGA TATARAN ERGATIVITAS DALAM BAHASA TAE’ - Gufran Ali Ibrahim (Masyarakat Linguistik Indonesia, 2013)
There are four basic clause types in Tae’, namely (1) intransitive ma-V and zero intransitive (ZI) clauses; (2) passive di- (di- PASS) clauses; (3) inherently transitive ma’- V, maN-V, mi-V, and nasal transitive (NT) clauses; and (4) zero transitive (ZT) clauses. Types (1), (2) and (3) are called absolutive constructions, while type (4) is an ergative construction. The Tae’ basic constituent order is VS/VAO. In the four basic clause types Tae’ shows a morphological ergative system. Within this system Tae’ uses the same set of absolutive person markers on verbs with S intransitive and O transitive, while a distinct set of ergative person markers is applied to verbs with A transitive. The pattern of introducing and maintaining participants in Tae’ discourse also reflects an ergative system. Participants in discourse tend to be introduced and maintained in S or O function. Participants are maintained in A function when a participant is made the topic. Discourse that introduces and maintains participants in this way is called ergative.